Mortality in primary resection of colon cancer in occlusion - Delgado, Bolívar; Cassinelli, Daniel (Cirugía del Uruguay, 1976)
A hundred cases of perforated chronic gastroduodenal ulcer are discussed. They were operated on ·b) severa! surgeons on the Hospital de Clínicas, of Montevideo. The most important conclusions of this analysis are reported, about the incidence, pathology, symptomatology, radiology, therapy and prognosis of this condition.